Scout as The Main Character in To Kill A Mockingbird, A Novel By Harper Lee - Asma Asma; Ida Muliawati (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2023)
Novel is entertaining for its readers and has other purposes, such as education, history, struggle, and social life, as seen from the characters presented. The study focuses on the characterization of the main character in the novel, Jean Louis Finch (Scout). To Kill a Mockingbird was written by Harper Lee and published in 1960. She is the best-known author and got the Publitzer Prize winning seller for her only novel. A qualitative method was adopted in data collection and analysis to achieve the study's objective. Specific questions were applied to identify and consider essential ideas and returned to the novel to locate specific evidence and passages related to the main character. Then, the actions, thoughts, words, expressions and other statements regarding the main character were described to find the analytical result. The result shows that the author develops the main character as an innocent little girl who continuously learns many things through life problems faced by his father. Moreover, the main character has an important role, making the store's plot more interesting.